Comparison of Integrated Biology Learning Citizen Science: World versus Indonesia - Gusti, Utari Akhir; Hidayat, Topik; Sriyati, Siti; Hamidah, Nur (Bioeducation Journal, 2024)
Integrated learning citizen science has become a major focus in the global education context. This study compares integrated learning approaches to citizen science between the world scope and its implementation in Indonesia. Citizen Science become innovative learning that combines community participation in scientific activities and provides opportunities for students to be actively involved in the process of scientific discovery during the learning process. This study compares learning citizen science, which is widely implemented in several countries in the world, with its implementation in Indonesia. This research is included in a systematic literature review (SLR) with PRISMA analysis. This study collects related articles on citizen science, which consists of 49 articles indexed by Scopus and SINTA, both international (35 articles) and national (14 articles), from various countries. The research results show that although the concept of citizen science has received global attention, its implementation in Indonesia still faces several unique challenges, including aspects of infrastructure, community participation, government support, and lack of guidance. However, there is great potential to develop this approach in a local context by taking into account the natural wealth and diversity of natural resources in Indonesia. This research provides a deeper understanding of the comparison between integrated learning citizen science on a global scale within Indonesia. These findings imply that the importance of adjusting strategies in order to approach citizen science can be integrated effectively into the educational context in Indonesia. This allows active community participation in sustainable scientific development with findings obtained through the integration of learning in schools.